Tailoring the catalytic performance of Cu/SiO2 for hydrogenolysis of biomass-derived 5-hydroxymethylfurfural to renewable fuels - Jia, Hongyan; Lv, Qing; Xia, Qineng; Hu, Wanpeng; Wang, Yanqin (Frontiers in Chemistry, 2022)
Efficient conversion of biomass-derived 5-hydroxymethylfurfural (HMF) to renewable fuels such as 2,5-dimethylfuran (DMF) and 2,5-dimethyltetrahydrofuran (DMTHF) is of significance for sustainable energy supply. For efficient catalyst design, it is important to understand the catalytic behavior and clarify the influence of physico-chemical properties of catalyst on reaction performance. Herein, to study the structure-activity relationships of monometallic Cu catalysts for HMF hydrogenolysis, a series of Cu/SiO2 catalysts with different physico-chemical properties were prepared and compared for their catalytic performance in HMF hydrogenolysis. It was found that Cu/SiO2-HT-8.5 catalyst prepared by hydrothermal method showed excellent activity in HMF hydrohydrolysis reaction. Under the optimal reaction condition, the total yield of liquid fuels reaches 91.6% with 57.1% yield of DMF and 34.5% yield of DMTHF in THF solvent. Characterizations such as XRD, H2-TPR, N2-adsorption/desorption, TEM and XPS revealed that the Cu particles in the Cu/SiO2-HT-8.5 catalyst have uniform size and high dispersion. The Cu species and the SiO2 support have relatively weak interaction and are easy to be reduced to Cu0, which makes it show excellent activity in the hydrogenolysis of HMF.